„Mały człowiek” we współczesnym świecie - Pudowa, Tatiana (Studia Rossica Posnaniensia, 2012)
The article analyzes the literary works of modern writers which are based on Gogol’s The Overcoat (Shinel). These stories and The Overcoat (Shinel) are united by a general theme – “the small person”. By addressing Gogol’s creativity the authors open up in what way the typical features of Gogol’s protagonist, Bashmachkin, have become true in the modern space.